Women's Empowerment Strategy Through Utilization of Yards as a Food Source - Nurhaeda Nurhaeda; Fitri Indahyani; Adriana K (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
This study aims to identify and analyze the internal factors which are the strengths and weaknesses as well as the external factors which are the main opportunities and threats and analyze and determine the appropriate strategies to be applied to empower women in supporting the food security of the communities. households. This research was designed using a survey method to collect data from the research objects, namely women members of the Women Farmers Group (KWT). The data obtained was then analyzed using a SWOT analysis to determine the empowerment model that would be applied in the form of activities aimed at using the yard to support household food security. The results of the identification of internal (strengths and weaknesses) and external (opportunities and threats) factors for the main factor of strength is the existence of good irrigation facilities and the main factor of weakness is the resulting product is not not sustainable. The most favorable opportunity factor is the market demand which continues to increase and the most influential threat factor is the limited availability of organic fertilizers and the ever fluctuating prices. The strategy of empowering women through the use of workcamps to support household food security which is the result of determining the right strategy is carried out from the results of the SWOT analysis based on the SWOT matrix increase and s Strive to use existing strengths, especially the power to have good irrigation facilities so that production can continue. The results of recommendations based on the SWOT matrix optimize the workforce and improve the quality of KWT members by following technological developments and government policies to produce maximum and quality output.